2011
DOI: 10.1016/j.jnucmat.2010.11.072
|View full text |Cite
|
Sign up to set email alerts
|

Isotope exchange experiments on TEXTOR and TORE SUPRA using Ion Cyclotron Wall Conditioning and Glow Discharge Conditioning

Abstract: This contribution reports on isotope exchange studies with both Ion Cyclotron Wall Conditioning (ICWC) and Glow Discharge Conditioning (GDC) in TEXTOR and TORE SUPRA. The discharges have been carried out in H 2, D 2 (ICWC and GDC) and He/H 2 mixtures (ICWC). The higher reionization probability in ICWC compared to GDC, following from the 3 to 4 orders of magnitude higher electron density, leads to a lower pumping efficiency of wall desorbed species. GDC has in this analysis (5-10) times higher removal rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…The modeled neutral flux is in the range of the neutral flux that was predicted from partial H 2 , HD and D 2 pressures, gas injection data and machine pumping speeds on TEXTOR, published in [39]. Also on TEXTOR the charged particle flux on a toroidal limiter blade, with a 0.5 m 2 surface, was measured.…”
Section: Textor H 2 -Icwc Dischargesmentioning
confidence: 89%
See 2 more Smart Citations
“…The modeled neutral flux is in the range of the neutral flux that was predicted from partial H 2 , HD and D 2 pressures, gas injection data and machine pumping speeds on TEXTOR, published in [39]. Also on TEXTOR the charged particle flux on a toroidal limiter blade, with a 0.5 m 2 surface, was measured.…”
Section: Textor H 2 -Icwc Dischargesmentioning
confidence: 89%
“…Also charged particles, due to their collective drifts, diffusion across the magnetic field, and transport along the field lines will interact with the walls. To describe the wall interaction in the model, the exchange of particles between wall and plasma is represented by the recycling coefficient R. From analysis of TEXTOR and TORE SUPRA mass spectroscopy data it is found that particle recycling in ICWC plasmas can be up to R ≥ 0.99 [39]. The recycling in the model is assumed to be immediate.…”
Section: Edge Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, that this is not meant to imply that the concentration, although it may have a substantial impact on coupling, is a control parameter. Detailed study and information about the isotope exchange parameters are provided elsewhere [11,17] and beyond the scope of present paper. The radial line-averaged density profile, derived from the multichannel (vertical) FIR interferometer data, is similar to that obtained in TEXTOR ICWC discharges in (He + H 2 ) [18], as shown in Fig.…”
Section: Study Of Antenna-plasma Coupling During Isotope Exchange In Jetmentioning
confidence: 99%
“…Эффективность обезгаживания увеличивается при работе короткими и м-пульсами (0,3 с -импульс, 1,5 с -пауза). На конференции ИЦРК были посвящены пять отдельных докладов [11,[14][15][16][17].…”
Section: день третийunclassified